Analisis Pengaruh Manajemen Laba Terhadap Kinerja Keuangan Perusahaan (Studi Kasus Pada Perusahaan Unilever) - Sabina Dewanda Putri; Cherlita Anjani; Ratih Kusumastuti (UNIVERSITAS MARITIM AMNI SEMARANG, 2023)
This study aims to analyze the effect of earnings management on the company's financial performance. Earnings management is a practice carried out by companies in managing financial information with the aim of influencing stakeholders' perceptions of company performance. This study will use a quantitative approach with secondary data obtained from the financial statements of companies listed on the stock exchange. The analytical method used in this study is multiple linear regression, with the dependent variable of company financial performance and earnings management as the independent variable. In addition, this study will also control for other variables that can affect a company's financial performance, such as company size, financial leverage, and sales growth. The results of this study are expected to provide a deeper understanding of the effect of earnings management on the company's financial performance. If it is proven that there is a significant influence, the implication is the importance of oversight and transparency in financial reporting in order to avoid earnings management practices that can be detrimental to the interests of company stakeholders. .